Les évêques, les conflits et la paix aux portes de la Normandie : les exemples des diocèses de Chartres et d'Évreux (première moitié du XIIe siècle) - Grégory Combalbert (Tabularia)
The charters of the bishops of Chartres and Évreux give information about their involvement in local conflicts. All of them present themselves as peace makers, but the necessity of their intervention is not the same on the two sides of river Avre. Bishops try to define everyone’s right, they favour negociation and take decisions, most often in a way of arbitration, in order to establish a long-lasting peace. The acta of Chartres also cast a spotlight on the use of different means of episcopal constraint, particularly excommunication, intending to make recalcitrants accept peace and to defend episcopal authority too.